2015
DOI: 10.1038/bjc.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and prognostic significance of p16INK4A protein overexpression and transcriptionally active human papillomavirus infection in laryngeal squamous cell carcinoma

Abstract: Background:Human papillomavirus (HPV) infection is a powerful prognostic biomarker in a subset of head and neck squamous cell carcinomas, specifically oropharyngeal cancers. However, the role of HPV in non-oropharyngeal sites, such as the larynx, remains unconfirmed.Methods:We evaluated a cohort of 324 laryngeal squamous cell carcinoma (LSCC) patients for the expression of p16INK4A (p16) protein by immunohistochemistry (IHC) and for high-risk HPV E6 and E7 mRNA transcripts by RNA in situ hybridisation (ISH). p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
75
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 40 publications
16
75
3
1
Order By: Relevance
“…Recent reports suggest that p16 is not a reliable predictor of prognosis in LSCC. Young et al analyzed the clinical outcome of patients with LSCC stratified on the basis of p16 expression and concluded that there was no survival advantage among p16+ patients [31]. Consistent with most of the previous findings, our study suggests that HPV infection status is a more reliable surrogate marker than p16 for predicting survival in patients with LSCC.…”
Section: Tong Et Al: Prognostic Significance Of Hpc In Laryngeal Cancersupporting
confidence: 90%
“…Recent reports suggest that p16 is not a reliable predictor of prognosis in LSCC. Young et al analyzed the clinical outcome of patients with LSCC stratified on the basis of p16 expression and concluded that there was no survival advantage among p16+ patients [31]. Consistent with most of the previous findings, our study suggests that HPV infection status is a more reliable surrogate marker than p16 for predicting survival in patients with LSCC.…”
Section: Tong Et Al: Prognostic Significance Of Hpc In Laryngeal Cancersupporting
confidence: 90%
“…The authors concluded that positive HVP 16 and/or p16 have no prognostic value on treatment outcome of non-OPSCC. This is consistent with our findings, and several reports suggesting that p16 and /or HPV are not predictors of survival among LSCC [44], [28] and HPSCC [28]. Meshman et al [23] did not support p16 predicting for locoregional control or ORS in the larynx or hypopharynx.…”
Section: Discussionsupporting
confidence: 92%
“…Other retrospective studies of p16 in LSCC and HSCC agreed with the negative impact of p16 on outcome [44][45][46]. On the contrary, the pooled RTOG analysis of non-OPSCC by Chung et al [16] identified the positive prognostic role of p16 in combined subset analysis.…”
Section: Discussionmentioning
confidence: 87%
“…The authors concluded that validation of these results specifically in OPSCC patients is warranted to inform treatment decisions. Although we also see a significant association by HPV genotype across all sites (results not shown), we concentrated on OPSCC since the prognostic value of HPV status in non-oropharynx tumors has yet to be established [14, 15]. Two other groups in the United States conducted studies comparing HPV genotypes in OPSCC.…”
Section: Discussionmentioning
confidence: 99%